Semiotic analysis on Malangan Batik for elementary school mathematics learning - Dyah Worowirastri Ekowati; Arina Restian; Erna Yayuk; Kamariah Kamariah (Jurnal Elemen, 2022)
Among the cultural richness in Indonesia, one of which is the Malangan batik cloth. The use of Malangan batik cloth is not only for clothing and decoration needs but also becomes part of the subject matter. In elementary school learning, Malangan batik cloth is one of the learning materials for Arts, Culture, and Crafts. In the thematic learning applied in elementary schools, Arts, Culture, and Crafts subjects do not stand alone. However, it must be related to other subjects, one of which is mathematics. The reality, on the ground, most teachers find it difficult to link the two. Bridging the link between these two subjects is carried out through semiotic analysis with its six primary objects. This study aimed to conduct a semiotic analysis of Malangan batik for elementary mathematics learning. The research was conducted in a qualitative descriptive manner with an ethnographic approach. Data were collected through observation, documentation, and interviews with two elementary school mathematics teachers and two Malangan batik makers. The research period is January-March 2022. The results of the study found that elementary mathematics concepts (numbers, algebra, geometry, measurement, statistics, and capital selection) have been identified according to six primary semiotic objects, namely language, problem-situation, concepts, procedures, properties, and arguments. By understanding each semiotic object, Malangan batik has the potential to increase students' mathematical activities that are contextual, interesting, and meaningful for students.